Conflicted Identification in the Sex Education Classroom: Balancing Professional Values With Organizational Mandates. (September 2016) - Williams, Elizabeth A.; Jensen, Robin E.
Despite enormous resources spent on sex education, the United States faces an epidemic of unplanned pregnancy and sexually transmitted infections among young people. Little research has examined the role sex educators play in alleviating or exacerbating this problem. In this study, we interviewed 50 sex educators employed by public schools throughout a Midwestern, U.S. state about their experiences in the sex education classroom. Twenty-two interviewees communicated feelings of conflicted identification and provided examples of the ways in which they experienced this subjectivity in the context of their employment. We find these interviews shed light on the as-yet-understudied communicative experience of conflicted identification by delineating key sources of such conflict and discursive strategies used in its negotiation. Our results suggest that those who experience conflicted identification and who have a sense of multiple or nested identifications within their overarching professional identity may be safeguarded to some extent from eventual organizational disidentification.